Alternatif Tuak Biogas - Indri Dayana (Ability: Journal of Education and Social Analysis, 2022)
A research on the study on alternative tuak as biogas tested in the laboratories of Physics Academy Maritim Belawan on December 22, 2016. The tools and materials 1L tuak, ¼ tepek brown sugar already sliced. Prepare tools and materials, Take 1 liter of wine and brown sugar ¼ tepek alreasy sliced , fermented for 7 days, Biogas is ready for use. The results were tested by a fire. If the fire of life, meaning there is 85% ethanol. Based on the research of alternative wine as biogas has met as a fuel that can be used in everyday life.